Ancient Sturgeons Possess Effective DNA Repair Mechanisms: Influence of Model Genotoxicants on Embryo Development of Sterlet, Acipenser ruthenus - Gazo, Ievgeniia (Int J Mol Sci, 2020)
DNA damage caused by exogenous or endogenous factors is a common challenge for developing fish embryos. DNA damage repair (DDR) pathways help organisms minimize adverse effects of DNA alterations. In terms of DNA repair mechanisms, sturgeons represent a particularly interesting model due to their exceptional genome plasticity. Sterlet (Acipenser ruthenus) is a relatively small species of sturgeon. The goal of this study was to assess the sensitivity of sterlet embryos to model genotoxicants (camptothecin, etoposide, and benzo[a]pyrene), and to assess DDR responses. We assessed the effects of genotoxicants on embryo survival, hatching rate, DNA fragmentation, gene expression, and phosphorylation of H2AX and ATM kinase. Exposure of sterlet embryos to 1 µM benzo[a]pyrene induced low levels of DNA damage accompanied by ATM phosphorylation and xpc gene expression. Conversely, 20 µM etoposide exposure induced DNA damage without activation of known DDR pathways. Effects of 10 nM camptothecin on embryo development were stage-specific, with early stages, before gastrulation, being most sensitive. Overall, this study provides foundational information for future investigation of sterlet DDR pathways.